Conditioning of self-assembled monolayers at two static immersion test sites along the east coast of Florida and its effect on early fouling development - Thomé, Isabel; Bauer, Stella; Vater, Svenja Mareike; Zargiel, K.; Finlay, J. A.; Arpa Sancet, Maria Pilar; Alles, Maria; Callow, J. A.; Callow, M. E.; Swain, G. W.; Grunze, Michael; Rosenhahn, A. (Biofouling, 2014)
Among the first events after immersion of surfaces in the ocean is surface ‘conditioning’. Here, the accumulation and composition of the conditioning films formed after immersion in the ocean are analyzed. In order to account for different surface chemistries, five self-assembled monolayers that differ in resistance to microfouling and wettability were used. Water samples from two static immersion test sites along the east coast of Florida were collected at two different times of the year and used for experiments. Spectral ellipsometry revealed that conditioning films were formed within the first 24 h and contact angle goniometry showed that these films changed the wettability and rendered hydrophobic surfaces more hydrophilic and vice versa. Infrared reflection adsorption spectroscopy showed that the composition of the conditioning film depended on both the wettability and immersion site. Laboratory and field assays showed that the presence of a conditioning film did not markedly influence settlement of microorganisms.